The breeding system of Hyacinthoides non-scripta (Asparagaceae): assessing the role of geitonogamy with captive pollinators - Guitián, Javier; Guitián, Pablo (Plant ecology and evolution, 2022)
Background and aims – In self-incompatible species, geitonogamous pollen deposition can result in stigma clogging, with negative effects on cross-fertilisation and subsequently reduced fruit and seed set. In this work, using laboratory and field experiments with pollinators in captivity, we describe the reproductive system of Hyacinthoides non-scripta and analyse the effect of the different mechanisms of pollen transfer, trying to quantify the effect of geitonogamy on the reproductive success of the species. Material and methods – Using laboratory and field experiments with pollinators in captivity we evaluated the effect of the different types of pollen transfer. Key results – The results show that H. non-scripta is a self-incompatible species and the pollen tubes in autogamous and geitonogamous pollination are rejected at the base of the style. In the field experiments, the presence of geitonogamous pollen on the stigma did not prevent subsequent fertilization by xenogamous pollen, but it reduced seed production. Conclusion – This study provides evidence that natural rates of geitonogamy significantly reduce female fitness in plants with large numbers of flowers per inflorescence and show how experiments with captive pollinators can help quantify the intensity of this effect.